2017
DOI: 10.1021/acs.jproteome.6b00972
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Analysis of Human Airway Cilia Identifies Previously Uncharacterized Proteins of High Abundance

Abstract: Cilia are essential to many diverse cellular processes. Although many major axonemal components have been identified and studied, how they interact to form a functional axoneme is not completely understood. To further our understanding of the protein composition of human airway cilia, we performed a semi-quantitative analysis of ciliary axonemes using label-free LC/MSE which identified over 400 proteins with high confidence. Tubulins were the most abundant proteins identified, with evidence for 20 different is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 80 publications
4
60
0
Order By: Relevance
“…FAP57/WDR65 is also highly conserved throughout vertebrate species, and in humans, FAP57 is especially abundant in testes, respiratory tissue, and fallopian tubes (Fagerberg et al, 2014;Blackburn et al, 2017). We suggest that FAP57/WDR65 should be screened as a candidate gene for those patients with PCD whose mutations have not been identified in the more commonly known PCD loci.…”
Section: Function Of Fap57/wdr65 In Ciliary Motility In Other Speciesmentioning
confidence: 95%
See 1 more Smart Citation
“…FAP57/WDR65 is also highly conserved throughout vertebrate species, and in humans, FAP57 is especially abundant in testes, respiratory tissue, and fallopian tubes (Fagerberg et al, 2014;Blackburn et al, 2017). We suggest that FAP57/WDR65 should be screened as a candidate gene for those patients with PCD whose mutations have not been identified in the more commonly known PCD loci.…”
Section: Function Of Fap57/wdr65 In Ciliary Motility In Other Speciesmentioning
confidence: 95%
“…Although several studies have identified FAP57/WDR65 as a conserved component of motile cilia and flagella (Broadhead et al, 2006;McClintock et al, 2008;Arnaiz et al, 2010;Sigg et al, 2017;Blackburn et al, 2017), functional studies on fap57/wdr65 mutations are very limited. One report identified a missense mutation in WDR65 in a patient with Van der Woude syndrome, a cleft palate disorder, but this work did not establish a clear connection between the mutation and the cleft palate defects (Rorick et al, 2011).…”
Section: Function Of Fap57/wdr65 In Ciliary Motility In Other Speciesmentioning
confidence: 99%
“…Further analysis using circular dichroism spectroscopy revealed that this protein has a melting temperature above 85 C and can refold to its native state even after heating to 100 C. Biochemical and immunofluorescence studies in Chlamydomonas identified CCDC103 in both the cytoplasm and the cilium where it appeared to be arrayed along the entire axonemal length (King & Patel-King, 2015). CCDC103 has also been identified by mass spectrometry in human airway cilia (Blackburn, Bustamante-Marin, Yin, Goshe, & Ostrowski, 2017). Axonemal CCDC103 was found to be stable to high salt treatment but could be readily extracted with 0.3% Sarkosyl as were the outer dynein arms.…”
Section: Introductionmentioning
confidence: 99%
“…CCDC103 exhibits unusual biophysical properties including the formation of dimers and higher order structures that are stable to, or reform after, heating in the presence of detergent (King & Patel-King, 2015;Panizzi et al, 2012). CCDC103 has also been identified by mass spectrometry in human airway cilia (Blackburn, Bustamante-Marin, Yin, Goshe, & Ostrowski, 2017). CCDC103 has also been identified by mass spectrometry in human airway cilia (Blackburn, Bustamante-Marin, Yin, Goshe, & Ostrowski, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in conjunction with other transcriptional regulators, such as HNF1B and SOX5, further ciliary diversity is introduced for mechanosensory renal cilia and bronchiolar cilia, respectively (Gresh et al, 2004, Kiselak et al, 2010). Proteomic profiling studies have sought to define the components of motile cilia by dysregulating such transcriptional regulators and analysing the proteome of isolated cilia preparations using mass spectrometry (Choksi et al, 2014a, Blackburn et al, 2017, Ostrowski et al, 2002, El Zein et al, 2009, Campbell et al, 2016). Each of these studies has produced a list of cilia-associated proteins and accordingly a number of databases have been established.…”
Section: Introductionmentioning
confidence: 99%